Case of Acute Graft Failure during Suspected Humoral Rejection with Preserved Ejection Fraction, but Severely Reduced Longitudinal Deformation Detected by 2D-Speckle Tracking. (11th June 2014) - Clemmensen, Tor Skibsted; Eiskjær, Hans; Kofoed-Nielsen, Pernille B.; Høyer, Søren; Poulsen, Steen Hvitfeldt
Abstract : This case displays limited utility of left ventricular ejection fraction to detect acute graft failure due to microvascular vasculopathy and suspected humoral rejection. Despite severe and progressive graft failure, clinically and by right heart catheterizations, left ventricular ejection fraction remained unchanged, indicating need of more reliable noninvasive methods for graft function surveillance. Global longitudinal strain relates to clinical heart failure, filling pressure, and cardiac index during suspected humoral rejection and microvascular dysfunction in this HTX patient. We suggest routine monitoring of graft function by global longitudinal strain as supplement to routine left ventricular ejection fraction and diastolic Doppler measurements.